The Obscured Story of the International Criminal Police Commission, Harry Söderman, and the Forgotten Context of Antiziganism. Issue 3 (27th May 2017) - Selling, Jan
Abstract : The Interpol predecessor, the International Criminal Police Commission (ICPC), gradually came under the control of the Nazi Regime. Besides the task of combatting 'ordinary criminality', it, since 1934, had 'combatting of the Gypsy plague' on its agenda. The Swedish contacts were handled independently by the head of the Swedish forensic institute (SKA), Harry Söderman, who had good contacts with the ICPC presidents Heydrich and Nebe. This essay discusses, from a Swedish perspective but also with an international comparative view, critical and apologetic discourses on the ICPC Nazification and antiziganism. It focuses on available ICPC files at Riksarkivet and their archival surroundings, which lead to the Sandler Commission's investigation of police collaboration against the Scandinavian sabotage and resistance organization Wollweber. A main conclusion is that the informal network character of the ICPC and its lack of transparency discouraged critical reflections on this Nazification, and, to this day, obstructed a break with antiziganistic police traditions. In contrast to the independent inquiry commissions of Switzerland and Norway, which discuss the context of antiziganism and the ICPC, the selective governmental initiatives in Sweden have until now neglected the topic. The essay also discusses the problematic ICPC source material situation.